Near-infrared spectroscopy during cardiopulmonary resuscitation and after restoration of spontaneous circulation: a valid technology?. Issue 3 (June 2016) - Wik, Lars
Abstract : Purpose of review: This article explores the status of using near-infrared spectroscopy and reporting cerebral oximetry (rSO2 ) for cardiac arrest patients. Recent findings: Bystander cardiopulmonary resuscitation (CPR) patients have significantly higher rSO2 compared with no bystander CPR patients. It is unclear how quickly rSO2 changes with hemodynamic instability. rSO2 during mechanical CPR varies between 44 and 55% and manual CPR varies between 20 and 40%, representing a significant relative rSO2 increase. Studies have found a relationship between rSO2 and restoration of spontaneous circulation (ROSC) and rSO2 increase can be used as a sign of ROSC. rSO2 evaluation is effective for monitoring quality of resuscitation and neurological prognostication. It seems that cardiac arrest patients with good neurologic outcome have significantly higher rSO2 levels (CPC 1–2 median rSO2 68%, CPC 3–5 median rSO2 58%, P  < 0.01) and good neurologic outcome (CPC 1–2) increased 'in proportion to the patients' rSO2 levels irrespective of their ROSC status at hospital arrival'. However, most of the studies are small and a prospective outcome study focusing on rSO2 values is needed. Summary: Near-infrared spectroscopy and rSO2 have been used as a monitor during CPR, detection of ROSC, after ROSC, and during post-resuscitation care. Prospective, controlled, randomized clinical studies are needed to document their wide use.